ANALISIS PENGENTASAN KEMISKINAN DALAM PRESPEKTIF PERAN GENDER DI PEDESAAN (STUDI KASUS DI DESA KALANGAN KEC. MARGOMULYO KAB. BOJONEGORO) - Pujimulyatama, Andriyan (Jurnal Ekonomi Pembangunan, 2014)
The objectives of this study were 1) to determine the characteristics of poor households in the village districts circles. Margomulyo Kab. Bojonegoro. 2) To determine the influence of age, education and gender roles to the family income. 3) To determine whether there is a significant difference in income after the role of gender in poor households. This study uses primary data obtained from questionnaires with 53 poor households. The analytical tool used is multiple regression with dummy variables and different test average. The results of 53 studies that poor households 23 respondents or 43% of elementary education (SD), 20 respondents or 38% had not compleceted elementary school (SD) and 10 respondents or 19% educated Junior High School (SMP). Types of jobs available 100 respondents 53% peasants?livelihood. Working hours in a day on average 7-9 hours. Wages earned Rp 20,000 to Rp 30,000 per day and for women workersor wives who work at Rp 20,000 to Rp 25,000 per day. Education elementary and junior high school education has no statistically significant effect on the family income of poor households, while age and gender roles have a statistically significant influence on the family income of poor households, if age is 1 (productive) it will add to the family income by Rp. 4683.643. Gender roles if the values is 1 (any gender roles) it will add to the family income by Rp. 24624.815. And there is a difference between family income existing gender roles and no gender roles.